Pendidikan dan Gender dalam Perspektif Islam - Nur Asiyah; Sulaiman Ibrahim (Pascasarjana IAIN Sultan Amai Gorontalo, 2021)
This paper explores the growing problems of education and gender in Islam. Education is to create a gender-fair education in transforming Islamic theory of equality between men and women. Islamic teachings cover every aspect of life. Islam has been teaching and appreciating human rights principles since its inception (HAM). The main and important lessons are respect and appreciation for people and humanity. Islamic teachings concern the people very much who are looking for knowledge. Islamic education is the responsibility of every Muslim man and woman that has the same opportunities to achieve it.